2013
DOI: 10.1111/boer.12017
|View full text |Cite
|
Sign up to set email alerts
|

Output–employment Relationship Across Sectors: A Long‐ Versus Short‐run Perspective

Abstract: This paper investigates the nature of the output-employment relationship by using the Turkish quarterly data for the period 1988-2008. Even if we fail to find a long-run relationship between aggregate output and total employment, there are long-run relationships for the aggregate output with non-agricultural employment and sectoral employment levels for seven of nine sectors that we consider. However, a further investigation for the output and employment relationship within a shortrun perspective does not reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
2
12
1
Order By: Relevance
“…The cointegration results documented in Table 3 confirm long-run relationships among employment, value-added and wages for each of the 10 sectors considered. This finding aligns with conclusions of previous studies, such as those by Chletsos and Kollias (1997) for Greece, Aydiner-Avsar and Onaran (2010) and Sahin, Tansel, and Berument (2013) for Turkey, and Skare and Caporale (2014) for 119 economies, which also concluded cointegration relationships among employment, output and wages (with other explanatory variables in some cases). Although we found no study investigating both determinants (GDP and wages) of employment for Saudi Arabia, Alkhateeb et al (2017b,c) and Alkhateeb, Sultan, and Mahmood (2017) find long-run relationships between aggregate employment and GDP at the country level.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…The cointegration results documented in Table 3 confirm long-run relationships among employment, value-added and wages for each of the 10 sectors considered. This finding aligns with conclusions of previous studies, such as those by Chletsos and Kollias (1997) for Greece, Aydiner-Avsar and Onaran (2010) and Sahin, Tansel, and Berument (2013) for Turkey, and Skare and Caporale (2014) for 119 economies, which also concluded cointegration relationships among employment, output and wages (with other explanatory variables in some cases). Although we found no study investigating both determinants (GDP and wages) of employment for Saudi Arabia, Alkhateeb et al (2017b,c) and Alkhateeb, Sultan, and Mahmood (2017) find long-run relationships between aggregate employment and GDP at the country level.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…During the post-crisis period, sectoral output remains the main driver of employment in all sectors while the other variables are also influential in most sectors. Sahin, Tansel and Berument (2013) analyze the association between output and employment in Turkey using quarterly data from 1988 to 2008 at the aggregate country level and for nine sectors. Their empirical results show the absence of a long-run relationship between economic output and employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, opposing conclusions on the relationship between manufacturing output and employment have also been found in other empirical studies (Basu and Foley, 2011;Madden & Tuckewell, 1975;Sahin, Tansel & Berument, 2013,). Madden and Tuckewell (1975) investigated the relationship between output and employment disaggregated by sectors through the consideration of numerous sectors in the Australian economy and concluded that in most of these sectors the short-run fluctuations in output had no relation to aggregate employment.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Out of this debate came a number of studies that have attempted to investigate whether this relationship does exist or not. Many of these studies (Akçoraoğlu 2010;Landmann 2002;Lewis-Wren, 1986;Pehkonen;2000;Sawtelle, 2007;Smyth, 1986;Wah, 1997) found a link between output and employment while others (Madden & Tuckewell, 1975;Sahin, Tansel & Berument, 2013) found that no such relationship exists between these two variables, especially in the short-run. This means that a short-run shock in overall output is not directly linked to an increase or decrease in total unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation